Age-related variations in position and morphology of the temporomandibular joint in individuals with anterior openbite and crossbite: a multi-cross-sectional comparative study - Yanxi Chen; Jingxi Wang; Ying Li; Lingfeng Li; Nan Luo; Yan Wu; Hongwei Dai; Jianping Zhou (BMC, 2022)
Abstract Background This study aimed to compare the age-related positional and morphological characteristics of the temporomandibular joint (TMJ) between individuals with anterior openbite or crossbite and controls. Methods This multi-cross-sectional comparative study analysed cone-beam computed tomography images of 750 participants, equally divided into the openbite, crossbite, and control groups (OBG, CBG, and CG, respectively). Each group was further divided into five subgroups (8-11 years, 12-15 years, 16-19 years, 20-24 years, and 25-30 years). Measurements of the TMJ included the position of the condyles in their respective fossae and morphology of the condyles and fossae. Data were submitted to statistical analysis. The study adhered to the STROBE Statement checklist for reporting of cross-sectional studies. Results Condyles were positioned more posteriorly with increasing age in all groups, and the condylar position was more posterior in the OBG than in the CBG. The articular eminence inclination increased with age in all the groups. There were significant differences in the articular eminence inclination among the three major groups at the age of > 15 years, and the condylar path was flatter in the CBG than in the OBG. Conclusions Age-related morphological and positional characteristics of the TMJ differed considerably among OBG, CBG and CG. Contrary to CBG, OBG was found to have relatively posterior condylar position and steeper condylar path.